Violências contra a pessoa idosa no município de Porto Alegre : estudo comparativo em tempos de pandemia do Covid-19 - Navarrete, Samantha Sittart (2022)
The beginning of 2020 was atypical due to the SARS-CoV-2 pandemic, COVID-19. The elderly population was the highest risk group due to the high lethality of this virus. Circulation restrictive measures were necessary to protect the population, causing their distance and social isolation. Due to these factors, there was great concern about the possible increase in cases of violence against elderly people, especially during this period, when they were inmates in their homes, since it is known that most violence occurs in the victims' own homes. Due to these facts, this research aimed to evaluate the effect of the COVID-19 pandemic on violence against the elderly through the records of occurrences formalized in the Police Department for the Protection of the Elderly in the city of Porto Alegre in 2020. How method of comparison used the occurrences recorded in the year 2019, in which there was no pandemic. Document analysis was performed as a technical procedure for data collection. A total of 615 occurrences were evaluated for the months of April, August and December 2019 and 2020. In 2019, most records of the occurrence of violence against the elderly occurred in April, followed by August and after December. However, in 2020, during the covid-19 pandemic, there was a reversal in the months of registration, which were mostly carried out in December, mainly related to the periods of relaxation of social isolation restrictions. The main types of violence recorded were psychological (62.4%), financial (30.4%) and physical (18.7%). What can be statistically observed in the comparison between years, was that physical violence increased in 2020, while negligence was more reported in 2019. We still count as a worrying factor the complaints repressed due to the pandemic by COVID-19. These data highlight the importance of public policies and strategies for confronting and preventing violence against vulnerable people.